The Transplantation and Replacement of Thoracic Organs The Present Status of Biological and Mechanical Replacement of the Heart and Lungs - Cooper, David K. C.; Novitzky, Dimitri (Springer Netherlands, 1990)
It gives us great pleasure to contribute a short introduction outstanding book. This comprehensive work provides an to this important volume. immense fund of information, and will be an invaluable The transplantation of thoracic organs - heart,heart source of knowledge to physicians, surgeons, and scientists lung, lung - is a field of surgery that is expanding annually. for many years to come. The use of mechanical assist devices and artificial hearts to support patients awaiting transplantation is also developing rapidly, and further advances in this field may eventually April 1990 Christiaan Barnard lead to a totally implantable device that will function Cape Town, South Africa successfully for many years. It is therefore timely that such a volume as this should be made available to those who wish to be brought up-to date with the current state of knowledge in these related fields. The editors have done us all a great service in bringing together experts in every aspect of heart and Nazih Zuhdi lung transplantation and replacement to contribute to this Oklahoma City, USA Xl Preface The fields of the transplantation and replacement of thoracic Refinements in bioengineering have enabled mechanical organs have expanded immensely since the first human assist devices and the total artificial heart to support patients to-human heart transplant was performed in 1967. This successfully until a suitable donor becomes available